The Problem-Based Learning Model Assisted by Multimedia Teaching Materials Enhances Students’ Critical Thinking Skills and Interest in Learning Science - Gusti Ngurah Bagus Tirtayadnya; I Made Citra Wibawa; Ketut Suma (Journal of Education Reseach and Evaluation, 2026)
The current condition of education indicates that elementary school students’ critical thinking skills in science in Indonesia have not yet developed optimally and remain a serious challenge, as reflected in science literacy achievement that is still below the international average. Therefore, this study aims to analyze the effect of a Problem-Based Learning (PBL) model supported by multimedia instructional materials on fifth-grade students’ critical thinking skills and learning interest in science. This study employed a quantitative approach using a quasi-experimental research design, specifically a pretest–posttest nonequivalent control group design. The population consisted of 313 fifth-grade elementary school students, from which a sample of 130 students was selected using random sampling techniques. Data were collected through tests and questionnaires, with research instruments comprising critical thinking tests and learning interest questionnaires. Data analysis was conducted using one-way MANCOVA with the assistance of SPSS 27.0 for Windows. The results indicate significant differences in students’ critical thinking skills and learning interest in science between those taught using the Problem-Based Learning model supported by multimedia instructional materials and those taught using the conventional Problem-Based Learning model. It can be concluded that the Problem-Based Learning model supported by multimedia instructional materials results in higher improvements in students’ learning interest in science compared to the Problem-Based Learning model. The implication of the research is that the application of PBL assisted by teaching materials can help students in learning.